Extent to which Management Controls Systems are used in the Sri Lankan Manufacturing Sector - Kariyawasam, A.H.N. (My University, 2015)
Management Control Systems are important mechanisms enabling organization development, learning and innovation, as the primary objective of Management Control Systems is to ensure the achievement of organizational goals and objectives. The manufacturing industry in Sri Lanka which is the main contributor to the industry sector of the country has been growing steadily since the reintroduction of open economic policies in 1978. The main objective of this study is to analyse the extent to which management control systems are used in the Sri Lankan manufacturing sector. Review of literature on the subject indicates that the use of MCS in Sri Lankan companies is extremely low and that basic MCS are the main MCS used by these firms in the industry. Data for study was collected from a structured self-administered questionnaire which was forwarded to a sample population of 83 public quoted manufacturing companies operating in Sri Lanka. Of these companies 71 responded to the questionnaire. Structured interviews were subsequently conducted with the Chief Operating Officers of these companies to ensure accurate completion of questionnaire and to authenticate the data provided. Analysis of data reveal that basic, cost and risk MCS are used extensively by public quoted companies operating in the manufacturing sector of the country, whilst the use of revenue MCS is limited. In addition, findings from the study also reveal a positive correlation between MCS and firm size, and MCS and firm financial performance.
Keywords: management conrtol systems; Manufacturing industry in Sri Lanka